Patent foramen ovale closure in non-elderly and elderly patients with cryptogenic stroke: a hospital-based cohort study - Chen, Po-Lin; Wang, Chi-Sheng; Huang, Jin-An; Fu, Yun-Ching; Liao, Nien-Chen; Hsu, Chiann-Yi; Wu, Yu-Hsuan (Frontiers in Neurology, 2023)
Introduction The efficacy of patent foramen ovale (PFO) closure in the elderly population is unclear. We aimed to investigate the efficacy and safety of PFO closure in non-elderly and elderly patients. Methods Patients over 18 years of age with cryptogenic stroke (CS) or transient ischemic attack and PFO were prospectively enrolled and classified into two groups according to treatment: (1) closure of PFO (the PFOC group) and (2) medical treatment alone (the non-PFOC group). The primary outcome was a composite of recurrent cerebral ischemic events and all-cause mortality during the follow-up period. A modified Ranking Scale [mRS] at 180 days was recorded. The safety outcomes were procedure-related adverse events and periprocedural atrial fibrillation. The results between the PFOC and non-PFOC groups in non-elderly (<60 years) and elderly (≥60 years) patients were compared. Results We enrolled 173 patients, 78 (45%) of whom were elderly. During a mean follow-up of 2.5 years, the incidence of primary outcome was significantly lower in the PFOC group (6.2% vs. 17.1%, hazard ratio[HR] = 0.35, 95% CI 0.13–0.97, p = 0.043) in adjusted Cox regression analysis. Compared with the non-PFOC group, the PFOC group had a numerically lower risk of the primary outcome in both the elderly (HR 0.26, 95% CI 0.07–1.01, p = 0.051) and the non-elderly (HR 0.61, 95% CI 0.11–3.27, p = 0.574) groups. In addition, patients with PFO closure in the elderly group had a lower median mRS at 180 days (p = 0.002). The rate of safety outcome was similar between the non-elderly and elderly groups. Discussion PFO closure was associated with a reduced risk of the primary outcome in patients with PFO and CS in our total cohort, which included non-elderly and elderly patients. Compared to those without PFO closure, elderly patients with PFO closure had a better functional outcome at 180 days. PFO closure might be considered in selected elderly patients with PFO.